Safety and efficacy of smart tracheal occlusion device in diaphragmatic hernia lamb model. (2nd January 2021) - Basurto, D.; Sananès, N.; Bleeser, T.; Valenzuela, I.; De Leon, N.; Joyeux, L.; Verbeken, E.; Vergote, S.; Van der Veeken, L.; Russo, F. M.; Deprest, J.
ABSTRACT: Objective: To investigate the efficacy and safety of the 'smart' tracheal occlusion (Smart‐TO) device in fetal lambs with diaphragmatic hernia (DH). Methods: DH was created in fetal lambs on gestational day 70 (term, 145 days). Fetuses were allocated to either pregnancy continuation until term (DH group) or fetoscopic endoluminal tracheal occlusion (TO), performed using the Smart‐TO balloon on gestational day 97 (DH + TO group). On gestational day 116, the presence of the balloon was confirmed on ultrasound, then the ewe was walked around a 3.0‐Tesla magnetic resonance scanner for balloon deflation, which was confirmed by ultrasound immediately afterwards. At term, euthanasia was performed and the fetus retrieved. Efficacy of occlusion was assessed by the lung‐to‐body‐weight ratio (LBWR) and lung morphometry. Safety parameters included tracheal side effects assessed by morphometry and balloon location after deflation. The unoccluded DH lambs served as a comparator. Results: Six fetuses were included in the DH group and seven in the DH + TO group. All balloons deflated successfully and were expelled spontaneously from the airways. In the DH + TO group, in comparison to controls, the LBWR at birth was significantly higher (1.90 (interquartile range (IQR), 1.43–2.55) vs 1.07 (IQR, 0.93–1.46); P  = 0.005), while on lung morphometry, the alveolar size was significantly increased (mean linear intercept, 47.5 (IQR, 45.6–48.1) vs 41.9 (IQR, 38.8–46.1) μ m; P  = 0.03); whereas airway complexity was lower (mean terminal bronchiolar density, 1.56 (IQR, 1.0–1.81) vs 2.23 (IQR, 2.14–2.40) br/mm 2 ; P  = 0.005). Tracheal changes on histology were minimal in both groups, but more noticeable in fetal lambs that underwent TO than in unoccluded lambs (tracheal score, 2 (IQR, 1–3) vs 0 (0–1); P  = 0.03). Conclusions: In fetal lambs with DH, TO using the Smart‐TO balloon is effective and safe. Occlusion can be reversed non‐invasively and the deflated intact balloon expelled spontaneously from the fetal upper airways. © 2020 International Society of Ultrasound in Obstetrics and Gynecology